Multiple organ failure in the newborn - Roberto Aufieri; Simonetta Picone; Piermichele Paolillo (Hygeia Press di Corridori Marinella, 2014)
Multiple organ failure (MOF), or multiple organ dysfunction syndrome (MODS) as more recently known, is a clinical syndrome characterized by the failure of two, or more, organs which are unable to maintain homeostasis without intervention. Described causative factors for MODS in the neonatal period are sepsis, shock due to any cause, tissue hypoperfusion, prematurity, hypoxic ischemic encephalopathy, necrotizing enterocolitis (NEC), surgery, congenital heart disease and others. MOF can be considered as the final common pathway of immunological, cytokine and hormonal changes, occurred as physiologic re- sponse to different infectious or non-infectious inflammatory insults, who lead to systemic inflammation, a procoagulant state and progressive organ dysfunction. The clinical presentation of MODS can widely vary, depending on the primary causes, nature, number and severity of the organ systems involved. Pre-MODS conditions should be promptly identified and treated. In case of severe sepsis and septic shock, the available guidelines should be followed. When MODS already occurred, supportive care for single organ dysfunction should be provided and adequate oxygenation and organ perfusion maintained. More studies in term and preterm infants (with the development of specific neonatal scoring systems) are needed, to further understand neonatal MODS and assess strategies for early prevention and treatment.   Proceedings of the International Course on Perinatal Pathology (part of the 10th International Workshop on Neonatology · October 22nd-25th, 2014) · Cagliari (Italy) · October 25th, 2014 · The role of the clinical pathological dialogue in problem solving Guest Editors: Gavino Faa, Vassilios Fanos, Peter Van Eyken